2017
DOI: 10.3928/1081597x-20161019-03
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Ectasia After LASIK Combined With Prophylactic Corneal Cross-linking

Abstract: This report illustrates that the currently used prophylactic CXL protocol in combination with LASIK may not be effectively preventing corneal ectasia in every case. [J Refract Surg. 2017;33(1):50-52.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Patients' mean age was 30. 22 Efficacy in terms of distance cumulative Snellen visual acuity (20/x or better) is presented in Figure 1A. In total, 98% of the eyes obtained 20/25 or better, 87% of the eyes obtained 20/20 or better, and 11% of the eyes obtained 20/16 or better.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients' mean age was 30. 22 Efficacy in terms of distance cumulative Snellen visual acuity (20/x or better) is presented in Figure 1A. In total, 98% of the eyes obtained 20/25 or better, 87% of the eyes obtained 20/20 or better, and 11% of the eyes obtained 20/16 or better.…”
Section: Resultsmentioning
confidence: 96%
“…In their study, the intensity was 18 mW, while in ours, it was 30 mW and the treatment time was only 90 s. No study, including ours, has reported ectasia in prophylactic CXL and LASIK. However, Taneri et al [22] described a young patient that developed unilateral corneal ectasia after undergoing a combined surgery of LASIK and prophylactic CXL, and with a normal presurgical ophthalmic examination. Consequently, from the currently available literature, only one case out of 638 eyes treated with prophylactic CXL and LASIK developed an iatrogenic ectasia.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al compared the new DCR parameters from Corvis ST before and after combining TransPRK with prophylactic crosslinking (30 mW/cm 2 , 90 s, 2.7 J/cm 2 ) and found that prophylactic crosslinking diminishes the impairment in corneal biomechanics after TransPRK compared with cases that did not undergo CXL (Lee et al, 2017). However, since a biomechanics impairment was still evident in the crosslinked cases, the Xtra procedures did not seem to ensure ectasia does not happen (Taneri et al, 2017). In this study, SSI, which represents the biomechanical stiffness of corneal material (Eliasy et al, 2019), increased by around 15% in all groups when compared with preoperative, confirming that the Xtra procedures were effective in restoring at least part of the loss in biomechanics caused by the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that human corneas are weakened by only approximately 10% following creation of a 90-lm flap. 22 The need for optimization of the CXL-treatment after LASIK is supported by a very recent case report 23 describing a postoperative ectasia after LASIK Xtra. The eye was treated using 0.22% riboflavin for 90 seconds and after rinsing of the interface a radiant exposure of only 2.7 J/cm 2 was applied.…”
Section: Discussionmentioning
confidence: 99%